Citizen participation and its impact on performance in U.S. nursing homes - Amirkhanyan, Anna A. et al (American Review of Public Administration)
Fundamental to democratic societies, citizen participation is an important tool for promoting active, informed, and empowered citizenry as well as responsive and accountable administration. Past literature on citizen participation has focused on its determinants, forms, and prevalence. This study examines the relationship between a specific form of citizen participation$1 (Bclient participation$1 (Band organizational performance. We use hybrid data on U.S. nursing homes that combine a survey of nursing home administrators$1 (Bmanagerial practices with federal performance appraisal data. Our empirical findings suggest that more intense levels of client participation, such as the use of clients$1 (Bfeedback in decision-making, are positively associated with performance: They increase the overall five-star ratings and lower health deficiencies. In contrast, less intense client participation efforts, such as merely communicating with client/family groups, are not significantly related to performance. This study highlights the role of participation intensity, suggesting that public administrators should not only go beyond informing and listening to their stakeholders, but also take steps to use the obtained feedback in organizational decision-making. - Reproduced.s
Keywords: Hospitals - United States